Pengaruh Pupuk Lengkap dan Kitosan terhadap Pertumbuhan Anggrek Phalaenopsis Hibrida secara In Vitro - Halida Adistya Putri; Dewi Sukma (JURNAL CITRA WIDYA EDUKASI, 2021)
Tissue culture succes is affected by medium composition. Murashige and Skoog (MS) basic medium composition is a medium tissue culture made from pure chemical substances which relatively expensive. Complete fertilizer commonly used as a replacement for MS basic medium is a complete fertilizer, which is relatively inexpensive and practical. Besides use suitable of basic medium composition, the addition of certain organic compound can also increase growth, development and resistance to disease of plant, such as chitosan. The research aims were to study the effect of complete fertilizer and chitosan on growth of PLBs and planlet Phalaenopsis Orchid Hybrids. The results showed that the basic medium composition complete fertilizer (N: P: K = 20:20:20) (2 g L-1) can be used as an alternative basal medium, because it can be increased the number of leaves , PLBs and plantlets higher than MS1/2 medium. Chitosan 5 ppm could not increased PLBs clump growth.